The fusiform response to faces: Explicit versus implicit processing of emotion. Issue 1 (20th September 2011) - Monroe, Justin F.; Griffin, Mark; Pinkham, Amy; Loughead, James; Gur, Ruben C.; Roberts, Timothy P.L.; Christopher Edgar, J.
Abstract Regions of the fusiform gyrus (FG) respond preferentially to faces over other classes of visual stimuli. It remains unclear whether emotional face information modulates FG activity. In the present study, whole‐head magnetoencephalography (MEG) was obtained from fifteen healthy adults who viewed emotionally expressive faces and made button responses based upon emotion (explicit condition) or age (implicit condition). Dipole source modeling produced source waveforms for left and right primary visual and left and right fusiform areas. Stronger left FG activity (M170) to fearful than happy or neutral faces was observed only in the explicit task, suggesting that directed attention to the emotional content of faces facilitates observation of M170 valence modulation. A strong association between M170 FG activity and reaction times in the explicit task provided additional evidence for a role of the fusiform gyrus in processing emotional information. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.